PENGARUH KONSEP DIRI, MOTIVASI KERJA, DAN KETERAMPILAN MANAJERIAL TERHADAP EFEKTIVITAS KERJA ANGGOTA LEGISLATIF - GUMANTI M, ANDI USMAN (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objectives of this research are to study the competence causal flow model with path analysis. The research about variable of self concept and task motivation has direct affect on task effectiveness thought managerial skill. The research was conducted at The Legislative Members Poepleâs Representative Regional Council at Province of Special Administrative Megapolis Jakarta, 2007. With n = 65 selected randomly. The finding of research is as follows: (i) self concept has direct effect on managerial skill; (ii) work motivation has direct effect on managerial skill; (iii) managerial skill has direct affect on task effectiveness; (iv) self concept has indirect effect on task effectiveness thought managerial skill; (v) work motivation has indirect effect on task effectiveness thought managerial skill. Based on of research findings, task effectiveness of Legislative Members could be enhanced by managing self concept, work motivation and managerial skill. Competence of Legislative Members to prove function and authority about legislation, budgeting, and controlling on regional government at Province of Special Administrative of Megapolis Jakarta.Keywords: managerial skill,Â self concept has indirect effect, managerial skill; and work motivation